Pain characteristics and psychological factors that mediate the association between obesity and outcomes of interdisciplinary pain rehabilitation: a registry-based cohort study - Huan-Ji Dong; Agnes Genander; Elena Dragioti (Annals of Medicine)
Background Obesity is a common comorbidity with chronic pain and is closely related to functional and psychological complications of pain, which are also the main outcomes of interdisciplinary pain rehabilitation programmes (IPRP). How obesity influences IPRP outcomes is poorly understood. This study aims to investigate the role of pain characteristics and psychological factors before IPRP as mediators of the association between obesity and IPRP outcomes (i.e. pain intensity and psychological functioning).Methods Sociodemographic variables, pain characteristics and psychological factors were retrieved from the Swedish Quality Registry for Pain Rehabilitation (SQRP). Data at baseline (pre-IPRP) and 1-year follow-up (FU-IPRP) were used in mediation analysis.Results Of the 872 patients (mean age 45.8 ± 10.5 years, 80.3% female), 232 (26.6%) were obese (body mass index [BMI] ≥ 30 kg/m2). Patients with obesity reported higher pain intensity (p = 0.02), a higher number of pain locations (p < 0.001), and longer pain duration (p = 0.002) compared to non-obese patients. Significant improvements at FU-IPRP were found in pain intensity and psychological functioning for both obese and non-obese groups. Mediation analysis revealed that pain intensity, pain radiation and depressive symptoms at pre-IPRP reduced the improvement of pain intensity at FU-IPRP among the patients with obesity. Depressive symptoms and pain intensity (or pain radiation) also mediated changes in two psychometric outcomes of IPRP (dysfunctional scale and adaptive coper scale).Conclusion At FU-IPRP, patients with obesity experienced improvements in pain and psychological well-being, which were mediated by pain intensity, pain radiation, and depression. The roles of these mediators need to be specifically addressed when designing a tailored IPRP for pain patients with comorbid obesity.